Socialization Impact Social Media Use in the Village Youth Against Nyarumkop - Resy Nirawati; Mariyam Mariyam; Sri Mulyani; Haris Rosdianto (STKIP Singkawang, 2018)
Event PPM is one of dedication to the community listed in the Tri Dharma College. The PPM activities conducted involving several professors, students, teenagers around the village Nyarumkop and some employees of the village. Measures undertaken in the form of socialization about the impact of social media for teens in the Village of East Singkawang Nyarumkop in the district in 2017. The method used in the service activities of these activities are lectures, discussions and question and answer. Results of implementation and yag response was obtained from the participants can be concluded that the purpose of these activities successfully and on target. Hopefully with these activities can contribute to society as one application of the Tri Dharma College, especially community service.